The use of straightwire technique and myofunctional therapy to treat anterior open bite due to tongue thrusting (case report) - Budi Suhartono (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background : In contrast to the posterior teeth, which are still in occlusion, No incisal contact in the anterior part of the maxilla and mandibula between the vertical dimension is referred to as anterior open. Skeletal irregularity during the expansion of the intermaxillary gap and poor habits can both contribute to openbite. Tongue thrusting is one of the undesirable practices that might result in anterior openbite. Objective : This treatment's objective is to break negative habits by employing myofunctional therapy to develop a healthy swallowing pattern and train the posture of the tongue and lips while at rest. Case Report : A 19-year-old woman who protruded her tongue visited a dental office with the main complaint of an unattractive anterior open bite. She had an open bite of 12 12 21 22 dan 31 32 41 42, a Class II Division I subdivision Angle, a Class II skeletal relationship (protruding maxilla, retrusive mandibula, and bidental protrusive), an overjet of 6.87 mm, an overbite of 0.43 mm, and a Class II skeletal relationship. Case Management : myofunctional therapy combined with straightwire orthodontic treatment. Result : The anterior open bite is rectified, the overjet is reduced to 2,2 mm, and the overbite is increased to 2 mm after 16 months of therapy. The patient's poor swallowing pattern has improved, and their terrible tongue-trusting behavior has decreased. Conclusion : Straightwire method and myofunctional therapy are both effective treatments for anterior openbite repair brought on by tongue thrusting.